PS10:182 Nmda-positive neuropsychiatric lupus manifesting as weight increase and hyposmia. (21st March 2018) - Pamfil, C; Rednic, S; Catana, I; Deac Badaranza, M; Balint Gib, D; Vele, P; Bene, L; Damian, L
Abstract : Background: Among the clinical manifestation of systemic lupus erythematosus (SLE), neurolupus (NPSLE) is one of the hardest to identify. While active systemic diseases usually evolve with weight loss, the increase is generally associated with glucocorticoid therapy and immobilisation and rarely with hypothalamic inflammation. NMDA encephalitis, increasingly recognised, may be paraneoplastic or autoimmune. Material and methods: We present the case of a 20 year female student, with an SLE with juvenile onset, at 16, mainly with renal features and malar rash. She was in a prolonged remission on azathioprine, hydroxychloroquine, low-dose aspirin and 5 mg prednisone/day. However, after the exam session, she came for a significant weight increment (over 12 kg in 2 weeks), despite allegedly normal eating, accompanied by day-time sleepiness and hyposmia. The BMI, initially 22.5, increased to 27.1, with a 29.3% of body fat by screening impedancemetry. The analyses revealed a high ESR (90 mm/h), an increased AAN titer (1/1280), with high anti-DNA (1055), and an anti-NMDA titer of 933 IU/mL. All other tests, including lupus anticoagulant, anti-cardiolipin, and beta-2 glicoprotein IgA, IgG, anti-Ro, anti-La, and ribosomal P anti-TPO, anti-thyreoglobulin antibodies, FT4 and TSH, were normal. Cerebral MRI was unremarkable, as well as the organ involvement screening, including genital examination and PAP smear. Olfactory function measurement revealed a threshold score of 6 (normal 7–12) and an identification score of 11 (normal 12–15). She received 3 courses of methylprednisolone and cyclophosphamide courses, with slow weight decrease and normalisation after two months and some correction of hyposmia in more than six months. Conclusion: Rapid unexplicable weight gain and decreased olfactory perception in lupus may suggest neurolupus or NMDA encephalitis.